The Effects of Oxidation on the Antithrombotic Properties of Tea Lipids against PAF, Thrombin, Collagen, and ADP - Tsoupras, Alexandros (Foods, 2020)
Tea provides health benefits, while oxidation is part of tea processing. The effect of oxidation on the antithrombotic properties of tea lipid extracts was evaluated for the first time. Total lipids (TL) extracted from fresh tea leaves and commercial tea powder, before and after 30–60 min of oxidation, were further fractionated into neutral lipids (NL) and polar lipids (PL). The antithrombotic bioactivities of tea TL, PL, and NL were assessed in human platelets against the inflammatory mediator platelet-activating factor. PL were further assessed against thrombin, collagen, and adenosine diphosphate, while their fatty acid composition was evaluated by GC-MS. PL exhibited the strongest antithrombotic effects against all platelet agonists and were rich in omega-3 polyunsaturated (ω3 PUFA) and monounsaturated (MUFA) fatty acids. A decline was observed in the antithrombotic activities, against all platelet agonists tested, for PL after 60 min of oxidation, and on their MUFA content, while their overall ω3 PUFA content and ω6/ω3 ratio remained unaffected. A synergistic effect between tea phenolic compounds and PL protects them against oxidation, which seems to be the rational for retaining the antithrombotic biofunctionalities of PL at a considerable favorable cardioprotective level, even after 60 min of tea oxidation. More studies are required to elucidate the mechanisms of the favorable synergism in tea PL extracts.